Experimentation on enhancement of solar still performance - Sonia Z. Issaq; Shamil K. Talal; Aasim A. Azooz (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
This work presents new results from controlled experiments using well-designed and constructed single-inclination solar stills. The aim of these experiments is to explore methods for enhancing still performance by studying the individual effects of three types of methods. Specifically, the experiments investigate the actual effects of still basin water depth, the use of a sensible heat storage medium, and the treatment of the inner glass surface with waxy substances. The main distinction in this work is the use of solar stills that can achieve thermal efficiencies in excess of 40% under favourable weather conditions without any modification. This high efficiency level allows for meaningful analysis of the impact of modifications on still performance. The results indicate that still yield, productivity, and thermal efficiency decrease significantly when the water depth in the basin exceeds 6 cm. additionally, introducing black gravel in excess of a 2% gravel to water mass ratio in the still basin does not produce a significant change in still thermal efficiency. Treatment of the still inner glass surface with two types of waxy materials resulted in large drop in still performance.